Telemedicine Health Care Delivery: A Global Strategy during COVID-19 Pandemic and Its Optimisation for Homoeopathy in India - Manchanda, Raj Kumar; Ponnam, Hima Bindu; Rompicherla, Kiranmayee G.R.; Nayak, C (Homœopathic Links, 2022)
Background After the declaration of COVID-19 as a pandemic by the World Health Organisation, the physical medical consultations became almost impossible. Telemedicine (TM) health care delivery (HCD) seemed to be the only means to handle the crisis and served as a boon in the management of mild to moderate COVID-19 cases. The telemedicine practice (TMP) spread worldwide in no time, and the same was adopted even in homoeopathic consultations.Objective The aim of this study is to highlight the TM practice globally and its adoption in homoeopathy concerning notified guidelines by the Central Council of Homoeopathy, erstwhile National Commission for Homoeopathy, Ministry of AYUSH (Ayurveda, Yoga and Naturopathy, Unani, Sow-Rigpa, Siddha and Homoeopathy), Government of India.Conclusion TMP has become a necessity for easy access to essential and universal health care and to treat remotely located patients. The publication of these guidelines for homoeopathic consultations is timely to strengthen and encourage its usage in public HCD. There is a need to periodically evaluate its optimal integration in digital health care in the future.
Keywords: COVID-19; global opportunity; homoeopathy; India; Ministry of AYUSH; public health care delivery; telemedicine practice